Lamentation and Poetic Imagination of Psalm 22. A Dialogue with Ricoeur on Secularization and Eschatological Hope - René Dentz (Phainomena)
Psalm 22, profoundly marked by lamentation and the transition to hope, offers an opportunity to explore the convergence between Paul Ricoeur’s biblical hermeneutics and contemporary challenges of secularization and the absence of eschatology. The contribution articulates the experience of abandonment described by the psalmist with the need for a poetic imagination capable of re-signifying existence. Ricoeur provides tools to understand the performativity of this psalm, bridging the tensions between narrative, metaphor, and the dynamic of “the power to be” inherent in biblical language.